Tick Saliva and the Alpha-Gal Syndrome: Finding a Needle in a Haystack - Sharma, Surendra Raj; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2021)
Ticks and tick-borne diseases are significant public health concerns. Bioactive molecules in tick saliva facilitate prolonged blood-feeding and transmission of tick-borne pathogens to the vertebrate host. Alpha-gal syndrome (AGS), a newly reported food allergy, is believed to be induced by saliva proteins decorated with a sugar molecule, the oligosaccharide galactose-⍺-1,3-galactose (α-gal). This syndrome is characterized by an IgE antibody-directed hypersensitivity against α-gal. The α-gal antigen was discovered in the salivary glands and saliva of various tick species including, the Lone Star tick (Amblyomma americanum). The underlying immune mechanisms linking tick bites with α-gal-specific IgE production are poorly understood and are crucial to identify and establish novel treatments for this disease. This article reviews the current understanding of AGS and its involvement with tick species.